Disclosure Effect of Enterprise Risk Management, Corporate Governance, Corporate Social Responsibility on Corporate Value - Pratiwi, Julia Loviana; Abidin, Zaenal (PT. Riset Press International, 2024)
The purpose of this study is to ascertain the degree to which company value in banking sector companies is influenced by enterprise risk management, corporate governance, corporate social responsibility, and company value between 2019 and 2022. The description and verification method is the one that is employed. The author employs multiple regression analysis, correlation analysis, and coefficient of determination analysis as analytical techniques. The analysis's findings demonstrate that the degree of Company Value (Y) is significantly impacted by the ERM variable (X1). This is evident from the 0.275 t value and a probability (p) = 0.038 and a regression coefficient (β) of 0.032. Company Value (Y) is significantly impacted by the CG variable (X2). The regression coefficient (β) of 0.050 and the t value of 0.362 with probability (p) = 0.002 both demonstrate this. Company Value (Y) is significantly impacted by the CSR variable (X3). The t value of 0.530 and the regression coefficient (β) of 0.045, along with the probability (p) = 0.006, demonstrate this. Company Value (Y) is significantly and simultaneously impacted by the ERM, CG, and CSR variables